The development of student activity sheet on trigonometric material based on local culture - Lakapu, Meryani; Dosinaeng, Wilfridus Beda Nuba; Leton, Samuel Igo (Universitas Islam Negeri Raden Intan Lampung, 2021)
Mathematics and culture are two different things, but they have a very close relationship in everyday life included in learning activities. Therefore, this research aims to describes the process and results of developing student activity sheets based on local culture on Simple Trigonometric Function Graphs. This research type is research and development. The product developed in this research is a student activity sheet based on local culture on Simple Trigonometric Function Graphics. Student activity sheets are developed based on a modified 4-D development model, which consists of defining, designing, and developing. At the definition stage; conducted a preliminary analysis, student analysis, material analysis, task analysis and specification of learning objectives. At the design stage; The preparation of student activity sheets based on local culture is carried out, selecting the format and then doing the initial design. At the development stage; The design results are validated by the expert and then revised according to the expert's notes. From the results of the research and data analysis conducted by researchers, it was found that the student activity sheets developed had met the criteria for good learning tools because they were declared valid, practical and effective.